Stress and Strain in Perovskite/Silicon Tandem Solar Cells - Liu, Kong; Wang, Zhijie; Qu, Shengchun; Ding, Liming (Nano-Micro Letters, 2023)
Tandem solar cells based on metal halide perovskites are advancing rapidly during last few years [<a id="ref-link-section-d255311780e354" title="K.A. Bush, A.F. Palmstrom, Z.S.J. Yu, M. Boccard, R. Cheacharoen et al., 23.6%-efficient monolithic perovskite/silicon tandem solar cells with improved stability. Nat. Energy 2(4), 17009 (2017). https://doi.org/10.1038/nenergy.2017.9 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR1" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">1,<a id="ref-link-section-d255311780e354_1" title="F. Sahli, J. Werner, B.A. Kamino, M. Brauninger, R. Monnard et al., Fully textured monolithic perovskite/silicon tandem solar cells with 25.2% power conversion efficiency. Nat. Mater. 17(9), 820–826 (2018). https://doi.org/10.1038/s41563-018-0115-4 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR2" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">2, 29% efficiency by enhanced hole extraction. Science 370(6522), 1300–1309 (2020). https://doi.org/10.1126/science.abd4016 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR3" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">3,<a id="ref-link-section-d255311780e354_3" title="Y. Hou, E. Aydin, M. De Bastiani, C.X. Xiao, F.H. Isikgor et al., Efficient tandem solar cells with solution-processed perovskite on textured crystalline silicon. Science 367(6482), 1135–1140 (2020). https://doi.org/10.1126/science.aaz3691 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR4" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">4,<a id="ref-link-section-d255311780e354_4" title="D. Kim, H.J. Jung, I.J. Park, B.W. Larson, S.P. Dunfield et al., Efficient, stable silicon tandem cells enabled by anion-engineered wide-bandgap perovskites. Science 368(6487), 155–160 (2020). https://doi.org/10.1126/science.aba3433 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR5" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">5,<a id="ref-link-section-d255311780e354_5" title="J. Liu, M. De Bastiani, E. Aydin, G.T. Harrison, Y.J. Gao et al., Efficient and stable perovskite-silicon tandem solar cells through contact displacement by MgFx. Science 377(6603), 302–306 (2022). https://doi.org/10.1126/science.abn8910 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR6" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">6,<a id="ref-link-section-d255311780e354_6" title="D.P. McMeekin, G. Sadoughi, W. Rehman, G.E. Eperon, M. Saliba et al., A mixed-cation lead mixed-halide perovskite absorber for tandem solar cells. Science 351(6269), 151–155 (2016). https://doi.org/10.1126/science.aad5845 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR7" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">7,<a id="ref-link-section-d255311780e354_7" title="J.X. Xu, C.C. Boyd, Z.S.J. Yu, A.F. Palmstrom, D.J. Witter et al., Triple-halide wide-band gap perovskites with suppressed phase segregation for efficient tandems. Science 367(6482), 1097–1104 (2020). https://doi.org/10.1126/science.aaz5074 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR8" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">8,<a id="ref-link-section-d255311780e354_8" title="L. Mazzarella, Y.H. Lin, S. Kirner, A.B. Morales-Vilches, L. Korte et al., Infrared light management using a nanocrystalline silicon oxide interlayer in monolithic perovskite/silicon heterojunction tandem solar cells with efficiency above 25%. Adv. Energy Mater. 9(14), 1803241 (2019). https://doi.org/10.1002/aenm.201803241 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR9" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">9,<a id="ref-link-section-d255311780e354_9" title="L. Liu, Z. Xiao, C. Zuo, L. Ding, Inorganic perovskite/organic tandem solar cells with efficiency over 20%. J. Semicond. 42(2), 020501 (2021). https://doi.org/10.1088/1674-4926/42/2/020501 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR10" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">10,<a id="ref-link-section-d255311780e354_10" title="J. Sun, L. Ding, Perovskite/organic tandem solar cells. J. Semicond. 44(2), 020201 (2023). https://doi.org/10.1088/1674-4926/44/2/020201 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR11" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">11,<a id="ref-link-section-d255311780e354_11" title="L. Liu, H. Xiao, K. Jin, Z. Xiao, X. Du et al., 4-terminal inorganic perovskite/organic tandem solar cells offer 22% efficiency. Nano-Micro Lett. 15(1), 23 (2022). https://doi.org/10.1007/s40820-022-00995-2 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR12" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">12,<a id="ref-link-section-d255311780e354_12" title="S. Chen, C. Zuo, B. Xu, L. Ding, Monolithic perovskite/silicon tandem solar cells offer an efficiency over 29%. J. Semicond. 42(12), 120203 (2021). https://doi.org/10.1088/1674-4926/42/12/120203 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR13" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">13,<a id="ref-link-section-d255311780e354_13" title="Y. Cheng, L. Ding, Perovskite/Si tandem solar cells: fundamentals, advances, challenges, and novel applications. SusMat 1(3), 324–344 (2021). https://doi.org/10.1002/sus2.25 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR14" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">14,<a id="ref-link-section-d255311780e354_14" title="Z. Fang, Q. Zeng, C. Zuo, L. Zhang, H. Xiao et al., Perovskite-based tandem solar cells. Sci. Bull. 66(6), 621–636 (2021). https://doi.org/10.1016/j.scib.2020.11.006 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR15" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">15,<a id="ref-link-section-d255311780e354_15" title="D. Zhao, L. Ding, All-perovskite tandem structures shed light on thin-film photovoltaics. Sci. Bull. 65(14), 1144–1146 (2020). https://doi.org/10.1016/j.scib.2020.04.013 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR16" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">16,<a id="ref-link-section-d255311780e357" title="Q. Zeng, L. Liu, Z. Xiao, F. Liu, Y. Hua et al., A two-terminal all-inorganic perovskite/organic tandem solar cell. Sci. Bull. 64(13), 885–887 (2019). https://doi.org/10.1016/j.scib.2019.05.015 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR17" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref" aria-label="Reference 17">17]. The certified power conversion efficiency (PCE) for monolithic perovskite/silicon tandem solar cell reaches 32.5% [<a id="ref-link-section-d255311780e360" title="NREL, "Best Research-cell Efficiency Chart," www.nrel.gov/pv/cell-efficiency.html Accessed: 20 Dec 2022" href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR18" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref" aria-label="Reference 18">18]. Since tandem solar cells contain more layers than single-junction solar cells, stress/strain control is an issue during fabrication and further practical operation. The stress can not only affect the stability of the perovskite layer but also change the optoelectronic properties of the films [<a id="ref-link-section-d255311780e363" title="M. Dailey, Y.N. Li, A.D. Printz, Residual film stresses in perovskite solar cells: origins, effects, and mitigation strategies. ACS Omega 6(45), 30214–30223 (2021). https://doi.org/10.1021/acsomega.1c04814 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR19" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">19,<a id="ref-link-section-d255311780e363_1" title="H. Zhang, N.G. Park, Strain control to stabilize perovskite solar cells. Angew. Chem. Int. Ed. 61(48), e202212268 (2022). https://doi.org/10.1002/anie.202212268 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR20" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">20,<a id="ref-link-section-d255311780e363_2" title="B.W. Yang, D. Bogachuk, J.J. Suo, L. Wagner, H. Kim et al., Strain effects on halide perovskite solar cells. Chem. Soc. Rev. 51(17), 7509–7530 (2022). https://doi.org/10.1039/d2cs00278g " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR21" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">21,<a id="ref-link-section-d255311780e363_3" title="Y.A. Jiao, S.H. Yi, H.W. Wang, B. Li, W.Z. Hao et al., Strain engineering of metal malide perovskites on coupling anisotropic behaviors. Adv. Funct. Mater. 31(4), 202006243 (2021). https://doi.org/10.1002/adfm.202006243 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR22" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">22,<a id="ref-link-section-d255311780e366" title="J.P. Wu, S.C. Liu, Z.B. Li, S. Wang, D.J. Xue et al., Strain in perovskite solar cells: origins, impacts and regulation. Natl. Sci. Rev. 8(8), nwab047 (2021). https://doi.org/10.1093/nsr/nwab047 " href="https://link.springer.com/article/10.1007/s40820-023-01019-3#ref-CR23" data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref" aria-label="Reference 23">23].